Chitin-like Polysaccharides in Alzheimer's Disease Brains - Castellani, Rudy J.; Siedlak, Sandra L.; Fortino, Anne E.; Perry, George; Ghetti, Bernardino; Smith, Mark A. (Current Alzheimer Research, 2005)
The role of polysaccharides in the pathogenesis of Alzheimer disease (AD) is unclear. However, in light of studies indicating impaired glucose utilization in AD and increased activation of the hexosamine pathway that is seen with hyperglycemia, in the brains of patients with AD, aberrantly high levels of glucosamine may result in synthesis of glucosamine polymers such as chitin, a highly insoluble polymer of N-acetyl glucosamine, linearized by b1-4 linkages. To examine this further, we studied brain tissue at autopsy from subjects with sporadic and familial AD using calcofluor histochemistry. Calcofluor excites on exposure to ultraviolet light and exhibits a high affinity for chitin in vivo by interacting with b1-4 linkages. Amyloid plaques and blood vessels affected by amyloid angiopathy showed bright fluorescence. Moreover, treatment with chitinase, followed by b-N-acetyl glucosaminidase showed a decrease in calcofluor fluorescence. Since chitin is a highly insoluble molecule and a substrate for glycan-protein interactions, chitin-like polysaccharides within the brain could facilitate nucleation of amyloid proteins in various amyloidoses including AD.
Keywords: chitin